Часопис «Літературно-Науковий Вістник» («Вістник»): періодизація й наукова рецепція - Супрун, Людмила; Suprun, Ludmyla (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Предметом аналізу у статті стала періодизація й наукова рецепція «Літературно-Наукового Вістника» («Вістника») (1898−1939). Виокремлено три періоди функціонування часопису. Визначено роль Івана Франка, Михайла Грушевського і Дмитра Донцова в історії видання ЛНВ. Розглянуто наукові студії журналу. Акценто-вано на думці про те, що, зважаючи на масштабність «Літературно-Наукового Вістника» («Вістника»), його роль та значення в українському національному житті, часопис заслуговує на ретельне, ґрунтовне й усебічне наукове дослідження. The subject of analysis in the article was the periodization and scientific reception of “Literary-Scientific Herald” (“Herald”) (1898−1939). It is determined three periods of functioning of the magazine. It is proved that the first period of the magazine (1898−1906) was rightly called “Frankivsk”; editor in chief of his second, “Kiev” period (1907−1919) was M. Grushevsky; LSH of the third period (1922−1939) not without reason was called “Dontsov’s Herald”. It is considered the scientific studies of the magazine. The first comprehensive work was the monograph of J. G. Shapoval “And in Ukraine it is consecrated that word...” (Lviv, 2003). Considerable part of the monograph of S. A. Kost “West ukrainian press of the first half of the twentieth century...” (Lviv, 2006) is devoted to the analysis of “Literary-Scientific Herald”. The first period of the history of LSH is covered in the candidate’s thesis of G. Korbych (K., 1997). In the candidate’s thesis of M. V. Butyrina (K., 2001) is studied LSH of Lviv and Kiev periods. As an example of Ukrainian scientific journalism of XIX – early XX centuries “Literary-Scientific Herald” is analyzed in the doctoral thesis of N. V. Zelinska (K., 2004). LSH of Kiev edition became an independent subject of study in the candidate’s thesis of N. V. Cusina (K., 2002). In the candidate’s thesis of L. S. Pavlyuk (K., 1996) made a comparative analysis of journalistic creativity of V. Vynnychenko, M. Hrushevsky and D. Dontsov. The third period of the history of LSH is the subject of journalistic research in candidate’s thesis of M. P. Leskov (K., 1996). Fundamental research of the activity of Dmytro Dontsov at the post of editor of “Literary-Scientific Herald” (“Herald”) was the doctoral thesis of S. M. Kvit (K., 2000). In the candidate’s thesis of T. L. Sheptycka it is actualized 1922−1932 years of functioning of the magazine (K., 2005). Fragmentary research of LSH we find in a number of other works.
The Magazine “Literary-Scientific Herald” (“Herald”): Periodization and Scientific Reception
Keywords: «Літературно-Науковий Вістник» («Вістник»); І. Франко; М. Грушевський; Д. Донцов; періодизація; наукова рецепція; “Literary-Scientific Herald” (“Herald”); I. Franko; M. Hrushevsky; D. Dontsov; the periodization; scientific reception